2020
DOI: 10.1177/0897190020926841
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Pharmacist-Managed Hypertension Clinic in a Rural Primary Care Setting

Abstract: Objective: To describe clinical pharmacy services provided in a rural North Carolina primary care clinic and assess the impact of these services on systolic and diastolic blood pressures in patients with uncontrolled hypertension. Methods: This single-center, retrospective study evaluated change in systolic and diastolic blood pressures from baseline, percentage of patients with blood pressure reductions, percentage at The Eight Joint National Committee (JNC 8) goal blood pressure, percentage at care gap closu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…The average BP during our patients' last visit was <140/90 mm Hg, demonstrating BP goal achievement in an NP/PharmD-led clinic. This extends previous work showing that when a pharmacist is embedded into primary goal BP goals are achieved (Stallings et al, 2020). Furthermore, our results support a narrowing of range in BP for patients seen in this clinic.…”
Section: Discussionsupporting
confidence: 89%
“…The average BP during our patients' last visit was <140/90 mm Hg, demonstrating BP goal achievement in an NP/PharmD-led clinic. This extends previous work showing that when a pharmacist is embedded into primary goal BP goals are achieved (Stallings et al, 2020). Furthermore, our results support a narrowing of range in BP for patients seen in this clinic.…”
Section: Discussionsupporting
confidence: 89%
“…There is plenty of evidence to show the value that pharmacists can add to patient care, particularly in rural and underserved areas. For instance, rural pharmacists have been shown to improve vaccine accessibility, 25 hypertension management 26 and access to hormonal contraception. 27 Furthermore, a pharmacist prescribing for an ambulatory conditions or minor ailments program in Saskatchewan was associated with cost savings for the health care system as well as improved access for patients, 28 with a similar program currently under development for Ontario.…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacist‐managed clinics (PMCs) provide outpatient services such as medication therapy management (MTM), disease management and patient education 1 . Previous studies have shown that implementing MTM has a significant impact on enhancing medication adherence, improving clinical outcomes 2–9 and achieving cost‐effectiveness 10–14 …”
Section: What Is Known and Objectivementioning
confidence: 99%